1991
DOI: 10.1038/349494a0
|View full text |Cite
|
Sign up to set email alerts
|

PRP16 is an RNA-dependent ATPase that interacts transiently with the spliceosome

Abstract: The assembly of the spliceosome is an ATP-dependent process. The splicing factor PRP16 contains variations of several motifs that define the eIF-4A-like ATP-dependent RNA helicase family. The protein has now been purified and shown to exhibit RNA-dependent ATPase activity. PRP16 is required specifically for the second catalytic step of the splicing reaction in vitro. This function requires ATP binding and/or hydrolysis, which appears to be concomitant with release of the protein from the spliceosome. PRP16 may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
269
0
2

Year Published

1995
1995
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 324 publications
(283 citation statements)
references
References 51 publications
12
269
0
2
Order By: Relevance
“…An analogous strategy was used to determine the value of K m oligo for U 15 RNA with a (P-S) backbone [abbreviated U 15:29-OH,(P-S) ]+ Stimulation provided by 2) to yield K m oligo ϭ 13 mM for the phosphodiester oligonucleotide and K m oligo , 0+25 mM for the phosphorothioate oligonucleotide+ B: ATPase activity with subsaturating ATP•Mg (1 mM), 0+25 mM eIF4A and subsaturating U 20 RNA (3 mM) is inhibited by addition of U 20 DNA with a phosphodiester (Ⅲ ) or a phosphorothioate backbone (▫ )+ Normalized values were obtained by dividing the observed rate constants by the rate constant measured in the absence of inhibitory oligonucleotide+ Curves represent fits to simple inhibition model (Equation 5), yielding K i oligo ϭ 12 mM for the phosphodiester oligonucleotide and K i oligo , 0+25 mM for the phosphorothioate oligonucleotide+ U 15:29-OH,(P-S) was measured in the presence of an inhibitory oligonucleotide, U 20:29-H,(P-S) , which was included in the reaction to compete with U 15:29-OH,(P-S) for binding to eIF4A and thus increase K m oligo,app (Scheme 1)+ Figure 4B shows the effect of this inhibitor on the U 15:29-OH,(P-S) concentration dependence for ATP stimulation, giving observed K m oligo,app values of 5+7 and 11 mM with 1 and 2+5 mM U 20:29-H,(P-S) present+ With these K m oligo,app values and the value of K i oligo for U 20:29-H,(P-S) (24 nM, determined from Fig+ 4A), K m oligo for U 15:29-OH,(P-S) was calculated to be 0+12 mM according to Equation 1c+ K m oligo for this (P-S)-containing oligonucleotide is ;100-fold smaller than K m oligo for the analogous (P-O)-containing oligonucleotide (13 mM, Fig+ 3A)+ Another DEAD box protein, PRP16, also binds tightly to phosphorothioate oligonucleotides Given the unexpectedly strong interaction between eIF4A and phosphorothioate-substituted oligonucleotides, it was of interest to determine if other DEAD box proteins also bind (P-S)-containing oligonucleotides tightly+ The DEAD box protein Prp16 is an RNAdependent ATPase involved in pre-mRNA splicing (Schwer & Guthrie, 1991;Wang & Guthrie, 1998)+ U 20:29-H,(P-S) inhibited the ability of poly(U) RNA to stimulate Prp16's ATPase activity .3,000-fold more than the analogous (P-O)-containing oligonucleotide (data not shown)+ The rate constant measured for Prp16 saturated with poly(U) RNA was not affected by the presence of the inhibitory oligonucleotide, consistent with competitive inhibition+ Thus, Prp16, like eIF4A, appears to bind (P-S)-containing oligonucleotides considerably more tightly than (P-O)-containing oligonucleotides+ Dependence of oligonucleotide affinity on the number and position of phosphorothioate linkages within an oligonucleotide Inhibition constants were measured for oligo(U) DNA of varying lengths with (P-O) or (P-S) backbones (Table 1)+ For both (P-O)-and (P-S)-containing oligonucleotides, affinity increases as length is increased+ The ratio of the inhibition constants for (P-O) and (P-S) oligonucleotides of the same length isolates the effect of substituting (P-O) linkages with (P-S) linkages from the overall effect of changing oligonucleotide length (ratio, We also measured the inhibition constants for a series of U 20 DNA oligonucleotides containing a varying number of (P-S) linkages in an otherwise (P-O) backbone (Fig+ 5)+ As the number of (P-S) linkages increases, there is an increase in affinity, with an effect of four-to eightfold per added block of four or five (P-S) linkages+ In addition, the inhibition constants for different oligonucleotides containing equal numbers of (P-S) linkages are the same within error, suggesting that (P-S) linkages at different locations within the oligonucleotides provide similar incr...…”
Section: Substituting Phosphodiester Linkages With Phosphorothioate Lmentioning
confidence: 99%
“…An analogous strategy was used to determine the value of K m oligo for U 15 RNA with a (P-S) backbone [abbreviated U 15:29-OH,(P-S) ]+ Stimulation provided by 2) to yield K m oligo ϭ 13 mM for the phosphodiester oligonucleotide and K m oligo , 0+25 mM for the phosphorothioate oligonucleotide+ B: ATPase activity with subsaturating ATP•Mg (1 mM), 0+25 mM eIF4A and subsaturating U 20 RNA (3 mM) is inhibited by addition of U 20 DNA with a phosphodiester (Ⅲ ) or a phosphorothioate backbone (▫ )+ Normalized values were obtained by dividing the observed rate constants by the rate constant measured in the absence of inhibitory oligonucleotide+ Curves represent fits to simple inhibition model (Equation 5), yielding K i oligo ϭ 12 mM for the phosphodiester oligonucleotide and K i oligo , 0+25 mM for the phosphorothioate oligonucleotide+ U 15:29-OH,(P-S) was measured in the presence of an inhibitory oligonucleotide, U 20:29-H,(P-S) , which was included in the reaction to compete with U 15:29-OH,(P-S) for binding to eIF4A and thus increase K m oligo,app (Scheme 1)+ Figure 4B shows the effect of this inhibitor on the U 15:29-OH,(P-S) concentration dependence for ATP stimulation, giving observed K m oligo,app values of 5+7 and 11 mM with 1 and 2+5 mM U 20:29-H,(P-S) present+ With these K m oligo,app values and the value of K i oligo for U 20:29-H,(P-S) (24 nM, determined from Fig+ 4A), K m oligo for U 15:29-OH,(P-S) was calculated to be 0+12 mM according to Equation 1c+ K m oligo for this (P-S)-containing oligonucleotide is ;100-fold smaller than K m oligo for the analogous (P-O)-containing oligonucleotide (13 mM, Fig+ 3A)+ Another DEAD box protein, PRP16, also binds tightly to phosphorothioate oligonucleotides Given the unexpectedly strong interaction between eIF4A and phosphorothioate-substituted oligonucleotides, it was of interest to determine if other DEAD box proteins also bind (P-S)-containing oligonucleotides tightly+ The DEAD box protein Prp16 is an RNAdependent ATPase involved in pre-mRNA splicing (Schwer & Guthrie, 1991;Wang & Guthrie, 1998)+ U 20:29-H,(P-S) inhibited the ability of poly(U) RNA to stimulate Prp16's ATPase activity .3,000-fold more than the analogous (P-O)-containing oligonucleotide (data not shown)+ The rate constant measured for Prp16 saturated with poly(U) RNA was not affected by the presence of the inhibitory oligonucleotide, consistent with competitive inhibition+ Thus, Prp16, like eIF4A, appears to bind (P-S)-containing oligonucleotides considerably more tightly than (P-O)-containing oligonucleotides+ Dependence of oligonucleotide affinity on the number and position of phosphorothioate linkages within an oligonucleotide Inhibition constants were measured for oligo(U) DNA of varying lengths with (P-O) or (P-S) backbones (Table 1)+ For both (P-O)-and (P-S)-containing oligonucleotides, affinity increases as length is increased+ The ratio of the inhibition constants for (P-O) and (P-S) oligonucleotides of the same length isolates the effect of substituting (P-O) linkages with (P-S) linkages from the overall effect of changing oligonucleotide length (ratio, We also measured the inhibition constants for a series of U 20 DNA oligonucleotides containing a varying number of (P-S) linkages in an otherwise (P-O) backbone (Fig+ 5)+ As the number of (P-S) linkages increases, there is an increase in affinity, with an effect of four-to eightfold per added block of four or five (P-S) linkages+ In addition, the inhibition constants for different oligonucleotides containing equal numbers of (P-S) linkages are the same within error, suggesting that (P-S) linkages at different locations within the oligonucleotides provide similar incr...…”
Section: Substituting Phosphodiester Linkages With Phosphorothioate Lmentioning
confidence: 99%
“…In yeast, the second-step factors have been ordered with respect to an ATP-dependent event during the second step (Schwer & Guthrie, 1991;Horowitz & Abelson, 1993;Ansari & Schwer, 1995;Jones et al+, 1995)+ The RNA helicase Prp16p hydrolyzes ATP and is required for a conformational change that occurs in the spliceosome after the first step (Schwer & Guthrie, 1992)+ yPrp17p is required before or during this event; Prp18p and Slu7p are required afterwards (Umen & Guthrie, 1995b)+ A role for the yeast Prp22 in the second step of splicing has been shown more recently (Schwer & Gross, 1998), and it is proposed to act in conjunction with Slu7 and Prp18+ Rearrangements in the spliceosome after the first step are required to identify and position the 39 splice site for the second step+ After the first step of splicing, the highly conserved loop I of U5 snRNA plays an important role in aligning the two exons for the second-step catalytic site+ In yeast, this loop is essential for the second step; however, in humans it is not required (O'Keefe et al+, 1996;Segault et al+, 1999)+ The loop I uridines are likely involved in noncanonical base pairing with the exon sequences near the splice sites, which are weakly conserved compared to elements in the intron+ Additional interactions appear to be necessary for stabilization of the U5 snRNA and the two exons during the second step+ For example, the highly conserved U5 snRNP protein Prp8p crosslinks to both the 59 and 39 splice sites (Wyatt et al+, 1992;Teigelkamp et al+, 1995;Umen & Guthrie, 1995a, 1995b)+ In addition, Slu7p and yPrp17p have been linked genetically to the function of U5 snRNA loop I Seshadri et al+, 1996)+ Prp18p and Slu7p have been shown to physically interact (Zhang & Schwer, 1997); however, no other direct interactions have been shown between proteins required for the second step+ Studies of synthetic lethality suggest that there is a functional interaction between all the second-step factors (reviewed in Umen & Guthrie, 1995c)+ Alleles of PRP17 are synthetically lethal with alleles of SLU7, PRP16, PRP18, PRP8, SLT11, U5 snRNA, and U2 snRNA Umen & Guthrie, 1995a;Seshadri et al+, 1996;Xu et al+, 1998), implying specific, and possibly direct interactions+ Insufficient knowledge of the proteins and/or RNAs that interact with yPrp17p, and the function of this protein, severely limits our understanding of its role in the second step of pre-mRNA splicing+ Through co...…”
Section: Introductionmentioning
confidence: 99%
“…From the loss of the pre-mRNA specific protection band and the increase in the accumulation of the intron-plus-second exon protection band, it could be suggested that NS l protein enhances the formation of the spliceosomal complex but inhibits the second step in the splicing reaction. Thus, it could interfere with the function of the U2, U4/U6 and/or the U5 snRNPs which may be involved in the catalytic steps of splicing (Newman & Norman, 1992) or with the activity of the mammalian counterpart of the PRP16 factor, a non-snRNP yeast protein with RNAdependent ATPase activity acting in the spliceosome before the second splicing step (Schwer & Guthrie, 1991).…”
Section: Centro Nacional Dementioning
confidence: 99%